Integrated Platform for Autonomic Computing - Panayiotou, C.; Fytros, E.; Tsetsos, V.; Samaras, G.; Hadjiefthymiades, S.; Piquet, D. (2009 6th IEEE Annual Communications Society Conference on Sensor, Mesh and Ad Hoc Communications and Networks Workshops, 2009)
IPAC (integrated platform for autonomic computing) aims at delivering a middleware and service creation environment for developing embedded, intelligent, collaborative, context-aware services in mobile nodes. IPAC relies on short range communications for the ad hoc realization of dialogs among collaborating nodes. Advanced sensing components leverage the context-awareness attributes of IPAC, thus rendering it capable of delivering highly innovative applications for mobile and pervasive computing. IPAC networking capabilities are based on rumour spreading techniques, a stateless and resilient approach, and information dissemination among embedded nodes. Spreading of information is subject to certain rules (e.g., space, time, price). IPAC nodes may receive, store, assesses and possibly relay the incoming content to other nodes. The same distribution channel is followed for the dissemination of new applications and application components that "join the IPAC world".